Turbulent flow structure over rough side-wall surface under wave-against-current motion. (February 2022) - Hansda, Sunil; Debnath, Koustuv
An experimental study of periodic surface waves acting against the turbulent currents under the influence of smooth and rough side wall is presented. Flow structure for current alone, and combined wave against current flows over smooth and rough side walls were measured with Acoustic Doppler Velocimeter to resolve the changes in the mean flow and turbulence characteristics resulting from the interaction of the flow and the wall roughness. Turbulent velocity fluctuations were analysed to characterise the turbulence and coherent structures and integral length and time scales were evaluated from the autocorrelation function estimates. Further the Kolmogorov length scales were determined using energy dissipation rate. Results show that the dissipation rate is greater for wave against current flow compared to the current alone flow for rough side walls. The streamwise integral length scale at the measured locations reduced with the increase in wave frequency acting against the current flow. Close to the wall surface, the effect of roughness attenuated the integral length scale and increased the turbulent dissipation rate. Continuous wavelet transform (CWT) was used as a tool to detect and establish the average time and length scales of largest horizontal coherent structures that existed in the wave against current combined flow.